A Contrast-enhanced Ultrasound Grading of Lymphatic Vessels: A Correlative Study and A Therapeutic Suggestion to Secondary Limb Lymphoedema - Fu, Ping; Zhu, Jia; Liu, Zijie; Zhang, Shentao; Kishor, Shahi; Chen, Li; Liu, Zhengren; Zhang, Lili (Current Medical Imaging, 2025)
BackgroundVarious methods have been employed to evaluate secondary limb lymphedema, each with its own set of limitations.ObjectivesTo delve into a novel approach to lymphatic grading, specifically utilizing enhanced ultrasound for assessing lymphatic function, to compensate for the shortcomings of other methods to some extent.Materials and MethodsThe clinical and ultrasound data of 51 patients with secondary limb lymphedema from June 2022 to September 2023 were retrospectively analyzed. The characteristic ultrasound manifestations of all visualized lymphatic vessels were studied. A contrast-enhanced ultrasound grading of lymphatic vessels (Ceus-Clv) was formulated and applied to grade the 51 patients. The study also correlated Ceus-Clv with Campisi clinical stage, postoperative duration, and duration of edema.ResultsOut of 51 patients, there were 19 cases of Ceus-Clv I, 10 cases of Ceus-Clv II, 19 cases of Ceus-Clv III, and 3 cases of Ceus-Clv IV. The correlation coefficient (rs) between Ceus-Clv and Campisi clinical stages was 0.958 (P < 0.001). Similarly, the correlation coefficient between Ceus-Clv and postoperative duration was 0.824 (P < 0.001), and between Ceus-Clv and duration of edema was 0.763 (P < 0.001).ConclusionCeus-Clv grading is a safe, convenient, and effective method for assessing lymphatic vessel function in secondary limb edema. This method can accurately reflect the patient's lymphatic vessel function and the severity of edema, providing valuable guidance for the treatment of secondary limb edema.
Keywords: Lymphography